The effects of inorganic nitrate supplementation on muscular power and endurance across the menstrual cycle - Hogwood, A. C.; Ortiz De Zevallos, J.; Kruse, K.; Buckley, M.; De Guzman, J.; DeJong Lempke, A.; Weltman, A.; Allen, J. D. (Journal of Applied Physiology, 2024)
Oral inorganic nitrate (NO-3) supplementation increases nitric oxide (NO) bioavailability and may improve muscular power in males and females, although data in females are limited. Estrogen increases NO bioavailability and fluctuates throughout the menstrual cycle, with low levels in the early follicular (EF) phase and peaking during the late follicular (LF) phase. The purpose of the present study was to examine the effects of NO-3 supplementation on isokinetic peak power, maximal voluntary isometric contraction (MVIC) force, muscular endurance, and recovery from fatigue in healthy young females during the EF and LF phases of the menstrual cycle. Ten eumenorrheic females were tested in a double-blinded, randomized, placebo-controlled design. Participants consumed ~13 mmol NO-3, in the form of 140 mL beetroot juice (BRJ), or an identical NO-3-depleted placebo (PL), for ~5 days prior to visits and 2 h prior to testing. Plasma estradiol was elevated in the LF phase, and plasma nitrite and nitrate were elevated in the BRJ condition (P < 0.05). Although isokinetic peak power was unchanged, calculated maximal power (Pmax) and maximal velocity (Vmax) were significantly worsened in the BRJ treatment independent of the menstrual cycle phase (P = 0.02 and 0.03, respectively). Muscular endurance, MVIC, and fatigue recovery were unaltered by BRJ or the menstrual cycle. These data indicate that NO-3 supplementation decreased maximal power and velocity in females and suggest that the benefits of NO-3 supplementation previously found in males may not extend to young females.